Funcionalidad familiar y depresión en adolescentes del barrio Sauces Norte del Cantón Loja - Cedillo Carrión, Jamil Santiago (2024)
Family dysfunction, which is understood as the family environment that does not promote the development of its members, represents one of the factors that cause children and adolescents to present both learning and behavioral problems during their growth. This dysfunction is proposed as a cause of several behavioral and emotional disorders related to human development, among which we have depression. For this reason, the present investigation was proposed with the objective of determining the family dysfunctionality of adolescents from the Sauces Norte neighborhood and its relationship with the presence of depression in said population, developing a descriptive, quantitative, cross-sectional cohort study. A total of 82 adolescents participated in the study, of which 9.76% (n=8) belong to the age of 13 years, 43.90% (n=36) belong to the age range of 14 to 16 years and 46.34% (n=38) in the range of 17 to 19 years; 54.88% (n=45) are women, 100% (n=82) are single and 67.07% (n=55) are in high school, while 4.88% (n=4) do not have any school instruction. In relation to family functionality, 86.59% (n=71) were classified as moderately functional, 9.76% (n=7) as dysfunctional and 1.22% (n=1) as severely dysfunctional; Moderate depression was found in 6.10% (n=5) and severe depression in 2.44% (n=2). It was shown that there is a statistically significant relationship between family dysfunction and the presence of depression in adolescents. It is concluded that the greater the dysfunction perceived by the adolescent, the greater the probability of presenting depression